A bulk-micromachined soil moisture probe with a mixed-signal interface - Valente, A. (2002)
This paper presents a Multi-Chip-Module based (MCM) microsystem for irrigation management suitable for greenhouse environmental control. The proposed microsystem includes a soil moisture microsensor, analog interface and sigma-delta converter, and signal processing for digital filtering. A heat-pulse technique is used to determine the volumetric heat capacity and thus the water content of a porous media, such as the soil. This method is based on the Joule effect (heater probe) and on the Seebeck effect (temperature probe). By using CMOS standard processes (low-cost) and wireless capabilities, a wireless network architecture can be implemented for measuring the soil moisture at the plant root level.